Traumatic ulcers with a hidden cause: A case report. (2nd February 2021) - Chana, Pavneet; Ion, Daniela
Abstract : Oral ulceration is a common condition that can affect the oral mucosa, and patients often present in both primary and secondary care. There are a number of causes of oral ulceration, ranging from trauma to malignancy. The cause of the oral ulceration can be difficult to establish, especially when the history and investigations do not support an obvious cause. We report a case of a 19-year-old male who presented with a 2-month history of worsening oral ulceration. Despite further questioning and investigations, the cause of the oral ulceration remained elusive. CPD/Clinical Relevance: To understand the clinical presentation and causes of oral ulceration.